Antonio Negri: Revitalisasi “Kultur Silih Berbagi” - Djunatan, Stephanus (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2013)
According to Antonio Negri, one may recognize the modern culture with hegemonizing power of the Empire or the superstate which is a mutual symbiosis of liberal democracy and modern capitalism. On the one hand the Empire attempts to subjugate and to regulate whatever social domains inasmuch as there is no longer insurgent agents which are capable to live outside the political and economical structure of this power. On the other hand, the more the Empire regulates social life the more the social domains per se are becoming fluid and modifiable. This flexibility or fluidity of social domains embodies within a kind of social body, which Negri names as the multitude. Agents of this kind of adaptable collectivity inherently exhibit natural capability of sharing. The capability to share of the multitude makes the Empire difficult to completely defeat and to conquer the social life. In other words, the multitude opposes the power to unify everything under the single political and economical flag of The Empire. Negri argues for this resistant capablity as the biopolitics of the multitude against the disciplinary force of the Empire. Nowadays, the capability of sharing is something familiar for nearly all local cultures in Indonesian Archipelago. Negri’s account of the power of sharing of the multitude reminds us in order to revitalize this capability of sharing within our cultural heritages.